Radiosensitivity enhancement by combined treatment of nimotuzumab and celecoxib on nasopharyngeal carcinoma cells - Huang JF; Yuan XP; Pang QF; Zhang HW; Yu JH; Yang B; Zhou LY; Zhang FZ; Liu FJ (Dove Medical Press, 2018)
Jianfeng Huang,1,* Xiaopeng Yuan,2,* Qingfeng Pang,3 Haowen Zhang,4 Jiahua Yu,4 Bo Yang,1 Leyuan Zhou,1 Fuzheng Zhang,1 Fenju Liu4 1Department of Radiation Oncology, Affiliated Hospital of Jiangnan University, Wuxi, People’s Republic of China; 2Department of Radiation Oncology, Nantong Tumor Hospital, Affiliated Tumor Hospital of Nantong University, Nantong, People’s Republic of China; 3Department of Physiopathology, Wuxi School of Medicine, Jiangnan University, Wuxi, People’s Republic of China; 4State Key Laboratory of Radiation Medicine and Protection, School of Radiation Medicine and Protection, Medical College of Soochow University, Collaborative Innovation Center of Radiological Medicine of Jiangsu Higher Education Institutions, Jiangsu Provincial Key Laboratory of Radiation Medicine and Protection, Suzhou, People’s Republic of China *These authors contributed equally to this work Introduction: In this study, the radiation-enhancing effects of combined treatment with nimotuzumab, a humanized EGFR-blocking antibody, and celecoxib, a COX-2 selective inhibitor, in human nasopharyngeal carcinoma (NPC) cells were investigated. Materials and methods: 3-(4,5-Dimethylthiazol-2yl)-2,5-diphenyltetrazolium bromide and clonogenic survival assays were done to evaluate the combined cytotoxic and radiosensitizing effects of nimotuzumab or celecoxib or the combination on CNE1 and CNE2 cells. Western blot analysis was performed to identify the effect of nimotuzumab and/or celecoxib with or without irradiation on the cytoplasmic and nuclear EGFR signaling pathways in CNE2 cells. Results: Our results demonstrated that concurrent administration of nimotuzumab and celecoxib cooperatively enhanced the cytotoxicity and radiosensitivity of CNE2 cells but not CNE1 cells. The combination of both drugs with or without irradiation also cooperatively inhibited cytoplasmic and nuclear EGFR signaling pathways in CNE2 cells. Conclusion: Our results suggest a promising approach for the treatment of poorly differentiated NPC. Keywords: celecoxib, cyclooxygenase-2, epidermal growth factor receptor, nasopharyngeal carcinoma, nimotuzumab, radiosensitivity